Yoga posture recognition using the deep learning process - Islam, Abidul; Sadman, Zarif; Imran, Shah; Islam, Sazzadul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.